Health-Related Productivity Loss According to Health Conditions among Workers in South Korea - Lee, Dong-Wook (Int J Environ Res Public Health, 2021)
This study aimed to investigate the degree of health-related productivity loss (HRPL) for common health conditions. A total of 4197 workers participated in a web-based questionnaire survey from January to February 2020. HRPL was measured using the Work Productivity and Activity Impairment questionnaire, and a difference in HRPL was calculated for each common health condition. The burden of productivity loss due to each health condition was calculated by the product of the difference in HRPL scores and the percentage of participants who complained. The health conditions most strongly associated with increased HRPL were infertility treatment (30.6%), osteoporosis (25.9%), cancer (25.3%), gastric ulcer or duodenal ulcer (25.0%) and anaemia (23.9%). The most important health conditions in order of their magnitude of induced burden of productivity loss were fatigue, neck or shoulder pain, insufficient sleep, back pain, headache, common cold and flu, insomnia, anxiety and diarrhoea or constipation. HRPL is more strongly and importantly associated with the aforementioned health conditions. Occupational health managers should prioritise addressing health conditions strongly and importantly associated with HRPL when implementing health promotion programmes.